Integration of kinetic modeling and desirability function approach for multi-objective optimization of UASB reactor treating poultry manure wastewater - Yetilmezsoy, Kaan (ELSEVIER SCI LTD, 2012)
An integrated multi-objective optimization approach within the framework of nonlinear regression-based kinetic modeling and desirability function was proposed to optimize an up-flow anaerobic sludge blanket (UASB) reactor treating poultry manure wastewater (PMW). Chen-Hashimoto and modified Stover-Kincannon models were applied to the UASB reactor for determination of bio-kinetic coefficients. A new empirical formulation of volumetric organic loading rate was derived for the first time for PMW to estimate the dimensionless kinetic parameter (K) in the Chen-Hashimoto model. Maximum substrate utilization rate constant and saturation constant were predicted as 11.83 g COD/L/day and 13.02 g COD/L/day, respectively, for the modified Stover-Kincannon model. Based on four process-related variables, three objective functions including a detailed bio-economic model were derived and optimized by using a LOQO/AMPL algorithm, with a maximum overall desirability of 0.896. The proposed optimization scheme demonstrated a useful tool for the UASB reactor to optimize several responses simultaneously. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Desirability function; Kinetic modeling; Multi-objective optimization; Poultry manure wastewater; Up-flow anaerobic sludge blanket reactor; INFLUENT SUBSTRATE CONCENTRATION; ANAEROBIC-DIGESTION; REMOVAL; METHANE; SLUDGE; COD; ELECTROCOAGULATION; TEMPERATURE; OPERATION; Agriculture; Biotechnology & Applied Microbiology; Energy & Fuels